PEDAGOGICAL AND PSYCHOLOGICAL FEATURES OF IMPROVING STUDENTSʼ INNOVATIVE THINKING SKILLS (Scientific journal of the Fergana State University, 2024)
In the context of rapid technological development and the transformation of the labor market, the formation of innovative thinking skills in students becomes particularly important. To shed light on the pedagogical and psychological characteristics of improving innovative thinking skills in students.The Concept of Innovative Thinking: The main characteristics and components of innovative thinking are analyzed.Psychological Features of the Development of Innovative Thinking in Students: Age and individual characteristics of cognitive processes that influence the formation of innovative abilities are examined. Pedagogical Techniques and Methods for Improving Innovative Thinking: Effective methods aimed at developing creativity, imagination, and the ability to solve non-standard problems are presented.The Role and Significance of an Innovative Educational Environment: The impact of the surrounding environment on the formation of innovative thinking is analyzed.The annotation is intended for teachers, educators, psychologists, parents, and anyone interested in developing innovative abilities in students.To provide practical recommendations for improving the innovative thinking skills of students to enhance their competitiveness in the modern world.